Pengukuran Beban Kerja Mental pada Pekerja Kurir dengan Metode NASA-TLX - Hasanah, Witri; Amrullah, Ezar; Saputra, Wahyu Sidiq; Dewi, Adhisty Kartika (Fakultas Teknologi Industri, UNISSULA, 2025)
Online shopping behaviour is increasingly having significant implications for businesses in the freight forwarding sector. The convenience offered by the marketplace also encourages increased consumer demand for goods. Good handling of consumer goods is the key to the success of shipping companies such as PT ABX Limpung. However, the balance of worker workload is essential to study to create an ergonomic work atmosphere. This study aims to measure the level of mental workload for courier workers at PT ABX Limpung using the NASA-TLX method. The results of the workload measurement revealed that the cognitive workload of courier workers was at a very high level. The measurement indicator that has the highest value is task-related. Therefore, this research underscores the urgent need to improve courier workers' tasks. These improvements are crucial for maintaining a healthy work environment and ensuring the well-being of the workers. The practical implications of these findings for management are significant, as they can guide the development of methods and the expansion of the study's scope, address the limitations of this research, and contribute to the logistics and freight forwarding field.